2016
DOI: 10.1016/j.vaccine.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different vaccination strategies on IBV QX population dynamics and clinical outbreaks

Abstract: The extreme variability and rapid evolution of Infectious bronchitis virus (IBV) has always represented the key challenge for its control because of the limited cross-protection among different strains. Several experimental trials have proven a broadening of the protection spectrum when animals are vaccinated with multiple genotypes. Nevertheless, the conditions of vaccine administration in field are so different that the generalization of experimental results is, at least, questionable. In the present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…2). A previous study has ascribed this episode to a change in the vaccination scheme adopted by this company, which moved from a heterologous Mass+793B based vaccination to a Mass only vaccination leading to an increased viral circulation and clinical outbreaks number 4 . Moreover, experimental studies demonstrated a significant reduction in R 0 in vaccinated groups compared to unvaccinated ones 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). A previous study has ascribed this episode to a change in the vaccination scheme adopted by this company, which moved from a heterologous Mass+793B based vaccination to a Mass only vaccination leading to an increased viral circulation and clinical outbreaks number 4 . Moreover, experimental studies demonstrated a significant reduction in R 0 in vaccinated groups compared to unvaccinated ones 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most effective control measure is vaccine application, which proved to effectively reduce clinical signs emergence, infectious pressure and viral population size, at least when properly performed 4,5 . However, this approach cannot be considered a panacea, and some drawbacks cannot be denied.…”
mentioning
confidence: 99%
“…Several experimental [ 29 ] and field [ 21 ] studies confirmed the efficacy of vaccination schemes based on the protectotype concept [ 30 ]. However, the rapid spread and high virulence [ 27 ] of this new variant challenged the previously established control strategies and has forced their re-assessment and the development of new homologous vaccines.…”
Section: Introductionmentioning
confidence: 96%
“…To cover this lack of information, a large scale phylodynamic study has been performed based on the S1 protein hypervariable region analysis of strains sampled all over the world, from the first GI-19 lineage (alias QX genotype) detection to the end of 2015. Additionally, to better understand the GI-19 lineage fate after its introduction in a previously naïve county, the spreading and population variation patterns were evaluated with reference to Italy, a major poultry producing country, where, after the first description in 2005, this lineage established itself as the predominant one [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…QX type IBV was first isolated by Bozorgmehri-Fard et al in Iran, the incidence was 9.6% from 2010 to 2014 and 10% from 2014 to 2015 (Najafi et al, 2016).The present study shows a reduction in the frequency of occurrence rate of QX IBV, which may reflect the efficacy of combined Massachusetts and 793/B type IB vaccines. Epidemiological analysis of IBV in Italy and Spain indicated a causal relationship between Massachusetts plus 793/B vaccination and a decreased prevalence of QX (Franzo et al, 2016). Kahya et al detected IS-1494-06 like IBV strain in turkey, 2011 (Kahya et al, 2013).…”
Section: Tablementioning
confidence: 99%